Histopathological Profile of Therapeutic Doses of Methanolic Extract Combination of Tea and Mango Mistletoes in Cardiac of Preventive Hypertensive Rats (DOCA-salt) Model - Durrotul Hasanah; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2022)
Tea and mango mistletoes have to lower blood pressure by improving oxidative stress and endothelial dysfunction. The flavonoid compounds found in these two mistletoes act as antihypertensives. Hypertension is a risk factors that influences the incidence of cardiac disease. This study examines the histopathological of the cardiac of hypertensive rats (preventive model) after treatment of methanolic extract combination of tea and mango mistletoes. This study used a completely randomized experimental design with 25 Wistar rats in total for five treatments, namely negative control (-), positive control (+), treatment 1 (dose of 50 mg/kg BW), treatment 2 (doses of 100 mg/kg BW), and treatment 3 (doses of 200 mg/kg BW). In this study, Deoxycorticosterone acetate (DOCA) were used to induce hyperttension in experimental animals. Data were analysed with one-way ANOVA test using JAMOVI (version 1.1.9.0) and posteriori. There was a significant difference between all groups (p<0.05). Administration of a methanolic extract combination of tea and mango mistletoes as the preventive model can significantly reduce hypertrophy of cardiac muscle cells. This effect occured with a dose of 50 mg/kg BW, the optimal dose to reduce hypertrophy of cardiac muscle cells in Wistar rats male.